Ferroelectric behavior and spectroscopic properties of La-Modified lead titanate nanoparticles prepared by a sol-gel method. Issue 2 (February 2020) - Mostafa, M.; Alrowaili, Z.A.; Rashwan, G.M.; Gerges, M.K.
Abstract: The sol-gel method was used to prepare perovskite type (Pb1-1.5x Lax □0.5x )TiO3 (PLT) ceramics with x = 0.21, 0.22, 0.23, 0.24, 0.25 in order to investigate their structural, optical, and dielectric properties. The crystallite compounds were obtained by calcinating the mixture of PbCO3, TiO2, and La2 O3 at 1000 °C for different time periods. After 4 h annealing, PLT23 sample, approximately a very little secondary phases have been observed in the XRD spectrum of the PLT sample with 23% La content (PLT23). The presence of La dopants might have affected the tetragonality of the Lead titanate crystal structure. The PLT samples tolerance factor decreases from 0.991 as in x = 0.21 to 0.986 for x = 0.25. Hence, these structures tend, generally, to be in the perovskite phase as t ~ 1. In the doped ceramics, characteristic phase transitions were shifted to lower temperatures. The dielectric permittivity value showed the tendency of a slight increase with lanthanum addition and achieved its maximum εm (3649) at x = 0.23, then it decreases for higher concentrations of La. The samples' estimated average crystallite size ranged from 40 nm to 50 nm, the maximum crystallite size about (49.6 nm) at x = 0.23 La. The calculated bandgaps were 3.1, 3.26, 3.28, 3.08, and 3.12 for the PLT with 0.21, 0.22, 0.23, 0.24 and 0.25% La, respectively. The Curie constant C was obtained as the slope of the curve of the inverse values of εr vs. temperature. The highest C value (5.2 × 10 5 K) was measured for the 23% La sample. The sample with 23% La content appears to be notably distinguished in its structural, optical, and dielectric characteristics compared with other samples. Abstract : Materials science; Nanotechnology; Ceramics; Ferroelectrics; PLT; Sol-gel; Optical; Dielectric